Hybrid Limited Shoulder Surgical Management (HLSSM) Sayed Issa's Hybrid Shoulder Arthroscopic-Open Surgical Management - Sayed Issa Abdulhamid (Journal of Clinical Case Reports and Images, 2023)
Introduction The idea of HLSSM2 is to get the least easy surgical intervention, as arthroscopic surgery begins with examining the shoulder joint, and the location and size of the lesion are determined, then open over the lesion with an open surgical approach that is very limited for surgical repair; not using arthroscopic instruments but conventional surgical instruments in the second step. Figure 1 Figure 1. Methods Clinical experience with this technique consists of 44 cases over a period of thirty-one months, this study was from September 2020 to May 2023. All cases were done as outpatients and under general anesthesia. Results The mean duration of the operation was 35 minutes, and the minimum duration was 25 minutes. There was no major nerve or vascular injury in all cases. This technique is simple, safe, and good cosmetically satisfactory for all patients after full recovery about three months after the procedure, and it is cost-effective. One 43-year-old female patient suffered pain and stiffness during the first six months after surgery and was not very satisfied, she did not stop visiting us till now, she was not happy because of shoulder pain and tenderness. Conclusion It can be used by experienced hand surgeons in shoulder arthroscopy and in Mini Lateral Shoulder Approach (MLSA)3, especially in countries where shoulder arthroscopic release and repair with suture anchors are expensive4 or not available. This technique is not very simple but is available, safe, cosmetically satisfactory, and cost-effective.
Keywords: HLSSM